ANALISIS KOMPARASI PRESTASI BELAJAR DITINJAU DARI MINAT BELAJAR DAN IPK PADA MATA KULIAH STATISTIKA - Herlina Herlina (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2016)
The purpose of this study is to know the difference of the average of students learning achievement in the subject of Statistics in views of student learning interest and students cumulative achhievement index (IPK) and also to know the interaction between students learning interests and IPK. The population of this research are 209 students with the sample size is 146. The data in this research are analyzed using the tests of model assumptions : a normality test in eleven times, a homogeneity test in seven times, and an analysis of variance (ANOVA) using SPSS data processor. The results of this study is that there is a difference of the average of students learning achievement between high, medium and low learning interests with sig 0,03 <0,05, that between IPK <3,00 and IPK≥3,00 with sig 0,000<0,05, and there is no interaction between learning interest and IPK with sig 0,936> 0,05.